Physical injury reduction in mango fruit using improved harvesting methods - Elkashif, Mohamed; Mohamed, Tawhida; Elamin, Osman (Gezira Journal of Agricultural Science, 2015)
The traditional method of harvesting mango fruit in the Sudan is done by snapping the fruits by a hook attached to a long pole. The drop of fruits to the ground causes bruises and injuries to the fruits, making them unattractive and unmarketable with a short shelf-life. An experiment was conducted in a private orchard along the Blue Nile bank, Gezira State, Sudan, during the seasons 2012 and 2013. The objective of this work was to find out the effects of an improved picking pole and fruit receiving treatments on the reduction of harvest losses in fruits of three mango cultivars. Treatments consisted of three mango cultivars, namely, Abu Samaka, Alphonse and Kitchener, two types of picking poles; the traditional picking pole and improved picking pole and four  treatments: The fruits were dropped directly on the ground (control), fruits were received on either a stretched sheet of cloth, a sponge mattress or a long tapering plastic mesh sleeve fixed to a ring attached to the picking poles. Treatments were arranged in a split-split plot design with three replicates. Cultivars were assigned to the main plots, picking poles to the sub-plots and receiving treatments to the sub-sub plots. Results showed that the improved picking pole resulted in significantly lower weight loss as compared to the traditional picking pole. The cultivar Abu Samaka showed significantly higher weight loss as compared to the other two cultivars. The highest percentage of weight loss was obtained when the fruits were allowed to fall directly on the ground (control), followed by the sheet of cloth and finally sponge mattress, whereas the long sleeve treatment resulted in the lowest weight loss. The improved picking pole resulted in the lowest physical injury, while the traditional picking pole resulted in the highest.    The improved picking pole equipped with a long sleeve resulted in the lowest physical injury, followed by the sheet of cloth treatment, the sponge mattress, whereas, dropping the fruits directly on the ground resulted in the highest physical injury. Abu Samaka cultivar had the highest percentage of physical injury, followed by Alphonse and then Kitchener cultivar. Shelf-life was significantly extended by using the improved picking pole coupled with receiving fruits in the long sleeve. However, the long sleeve fruit receiving treatment took the longest time to harvest 100 mango fruits under both types of picking poles. It is recommended to harvest mango fruits using the improved picking pole coupled with receiving fruits in a long plastic mesh sleeve for the reduction of harvest losses.        حصاد المانجو في السودان يتم بإستخدام الخطاف وهو عبارة عن عصا طويلة مثبت بها خطاف معقوف وهذا يؤدى إلى سقوط الثمار على الأرض وإصابتها بالجروح والخدوش مما يقلل من نوعيتها وعدم صلاحيتها للتسويق. أجريت تجربة بواد مدنى، ولاية الجزيرة، السودان، في 2012 و 2013. الهدف من الدراسة هو ايجاد تأثير الخطاف المحسن ومعاملات إستقبال الثمار على تقليل الأضرار التي تصيب الثمار أثناء الحصاد لثلاثة أصناف من المانجو. إشتملت المعاملات على ثلاثة أصناف من المانجو وهى أبوسمكة والفونس وكتشنر ونوعين من الخطاف وهما الخطاف المحسن والتقليدي وأربعة معاملات لإستقبال الثمار وهى سقوط الثمار على الأرض مباشرة  (شاهد) واستقبال الثمار على قماش مشدود تحت الشجرة أو على مرتبة إسفنجية أو في خرطوم من شبكة البلاستيك مثبت على الخطاف. أستخدم تصميم القطع المنشقة المنشقة بثلاث مكررات. كانت أصناف المانجو القطع الرئيسية ونوع الخطاف القطع الفرعية ومعاملات إستقبال الثمار القطع الفرعية. أظهرت النتائج أن الخطاف المحسن أعطى معنوياً أقل نسبة لفقدان وزن الثمار بالمقارنة مع الخطاف التقليدي. الصنف أبوسمكة أعطى معنوياً أعلى معدل لفقدان الوزن مقارنة بالأصناف الأخرى. بالنسبة لمعاملات إستقبال الثمار، فإن وقوع الثمار على الأرض مباشرة أعطى أعلى معدل لفقدان الوزن ويليه وقوع الثمار على القماش ثم مرتبة الإسفنج، بينما أعطى إستقبال الثمار في خرطوم البلاستيك أدنى معدل لفقدان الوزن. الخطاف المحسن أعطى أدنى نسبة للإصابة بالأضرار مقارنة بالخطاف التقليدي. كذلك الخطاف المحسن المزود بخرطوم البلاستيك أعطى أدنى نسبة للإصابة بالأضرار يليه القماش المشدود تحت الشجرة ثم مرتبة الإسفنج ، بينما أدى سقوط الثمار على الأرض أعلى نسبة للإصابة بالأضرار. الصنف أبوسمكة أعطى أعلى نسبة للإصابة بالأضرار يليه الصنف الفونس ثم كتشنر. الخطاف المحسن المزود بخرطوم البلاستيك أعطى أطول فترة صلاحية للثمار ولكنه استغرق وقتاً أطول لحصاد مائة ثمرة. بناءً على هذه الدراسة فإنه يوصى بحصاد ثمار المانجو بإستخدام الخطاف المحسن المزود بخرطوم البلاستيك لتقليل تلف الثمار.